Clinical Consensus Statement: Septoplasty with or without Inferior Turbinate Reduction. (2nd November 2015) - Han, Joseph K.; Stringer, Scott P.; Rosenfeld, Richard M.; Archer, Sanford M.; Baker, Dole P.; Brown, Seth M.; Edelstein, David R.; Gray, Stacey T.; Lian, Timothy S.; Ross, Erin J.; Seiden, Allen M.; Setzen, Michael; et al.
Abstract : Objective: To develop a clinical consensus statement on septoplasty with or without inferior turbinate reduction. Methods: An expert panel of otolaryngologists with no relevant conflicts of interest was assembled to represent general otolaryngology and relevant subspecialty societies. A working definition of septoplasty with or without inferior turbinate reduction and the scope of pertinent otolaryngologic practice were first established. Patients 18 years and older were defined as the targeted population of interest. A modified Delphi method was then used to distill expert opinion into clinical statements that met a standardized definition of consensus. Results: The group defined nasal septoplasty as a surgical procedure designed to correct a deviated nasal septum for the purpose of improving nasal function, form, or both. After 2 iterative Delphi method surveys, 20 statements met the standardized definition of consensus, while 13 statements did not. The clinical statements were grouped into 8 categories for presentation and discussion: (1) definition and diagnosis, (2) imaging studies, (3) medical management prior to septoplasty, (4) perioperative management, (5) surgical considerations, (6) adjuvant procedures, (7) postoperative care, and (8) outcomes. Conclusion: This clinical consensus statement was developed by and for otolaryngologists and is intended to promote appropriate and, when possible, evidence‐based care for patients undergoing septoplasty with or without inferior turbinate reduction. A complete definition of septoplasty with or without inferior turbinate reduction was first developed, and additional statements were subsequently produced and evaluated addressing diagnosis, medical management prior to septoplasty, and surgical considerations, as well as the appropriate role of perioperative, postoperative, and adjuvant procedures, in addition to outcomes. Additionally, a series of clinical statements were developed, such as "Computed tomography scan may not accurately demonstrate the degree of septal deviation, " "Septoplasty can assist delivery of intranasal medications to the nasal cavity, " "Endoscopy can be used to improve visualization of posterior‐based septal deviation during septoplasty, " and "Quilting sutures can obviate the need for nasal packing after septoplasty." It is anticipated that the application of these principles will result in decreased variations in the care of septoplasty patients and an increase in the quality of care.